Increased coproporphyrin serum levels in healthy volunteers treated with the cholesterol uptake inhibitor ezetimibe - Kinzi, Jonny; Grube, Markus; Seibert, Isabell; Siegmund, Werner; Meyer zu Schwabedissen, Henriette E. (Clinical and translational science, 2024)
Ezetimibe undergoes glucuronidation that results in the active metabolite ezetimibe phenoxy‐glucuronide (ezetimibe‐glucuronide). This phase‐II metabolite was shown to interact with the clinically relevant hepatic transporter organic anion transporting polypeptide (OATP) 1B1. In recent years, coproporphyrin I (CPI) was established as a Tier 1 biomarker for OATP1B‐mediated interactions among other endogenous substrates like CPIII. To evaluate whether levels of the biomarker are affected by ezetimibe treatment, we assessed the impact of ezetimibe and ezetimibe‐glucuronide on OATP1B1‐mediated transport of CPs in vitro. Then, we quantified CP levels in serum samples of healthy volunteers treated with a single oral dose of ezetimibe (20 mg) alone or in combination with rifampin (600 mg). Results from our in vitro experiments showed a significant reduction in cellular CPI accumulation in the presence of ezetimibe‐glucuronide with an IC50 of 1.97 μM [95% CI: 1.04 to 3.96], while CPIII accumulation was impacted by 10 μM and above. In the in vivo study, we observed peak CP concentrations 1.33 h after dosing, which is closest to the tmax of the ezetimibe metabolite. Co‐administration of ezetimibe with rifampin resulted in even higher serum CP levels. The AUC0–24h of CPI and CPIII increased two‐ and threefold, respectively, after concomitant dosing compared to ezetimibe alone. Moreover, we quantified CP levels in cumulative urine from both study phases where the renally excreted amount (Ae) of CPI and CPIII increased after ezetimibe and rifampin co‐administration compared to ezetimibe alone. In conclusion, our findings indicate that rifampin co‐administration results in additional inhibition of OATP1B1 in vivo.